Changes in player activity profiles after the 2015 FIH rule changes in elite women's hockey - McMahon, E. G.; Kennedy, A. R. (The Journal of Strength and Conditioning Research, 2019)
The aim of this study was to compare the player activity profiles of elite international women's hockey players before (2014) and after (2015) the 2015 the International Hockey Federation (FIH) match rule changes at team and positional levels. The match activity profiles (n = 400) of 19 female hockey players (age 23 ± 4 years, mass 63.6 ± 5.5 kg, VO2max 57 ± 6 ml·kg-1·min-1 in 2014, 58 ± 6 ml·kg-1·min-1 in 2015) were recorded during competitive international matches in 2014 (match n = 12) and 2015 (match n = 13) using 10-Hz global positioning system units. The practical utility of an effect was only classified as substantial when there was a >75% likelihood that the ±90% confidence interval of the effect size (ES) was equal to or greater than the small (ES ± 0.2) reference value. Mean match time decreased by over 2 minutes from 71.72 ± 1.38 to 69.40 ± 4.72 minutes. There were increases at the team level in relative substitutions (SUB), relative distance (RD), high-speed running (HSR: 3.08-5.27 m·s-1), and surges (S), with a fall in low-speed running (LSR: 0-3.05 m·s-1) between 2014 and 2015. There were no changes in the between-position differences observed from 2014 to 2015. Within positions, there were relative increases in RD for all positions, HSR and S for midfield, and in SUB and S in forwards. The 2015 FIH rule changes seem to have increased the general intensity of international women's hockey. However, the different facets of physical performance did not change uniformly across team positions. Therefore, specific modifications to conditioning practices for each position may be warranted to more accurately reflect match demands.